2022
DOI: 10.1097/aog.0000000000004983
|View full text |Cite
|
Sign up to set email alerts
|

Association of Myomectomy With Anti-Müllerian Hormone Levels and Ovarian Reserve

Abstract: Myomectomy is associated with a short-term decline in serum anti-müllerian hormone levels; however, no long-term change in ovarian reserve, as measured by anti-müllerian hormone levels, is observed, regardless of route of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Similar to RT regarding the effect of uterine surgery on ovarian reserve, Aharon et al reported on AMH before and after myomectomy 14 . Their study found a significant decrease in AMH at 2 weeks postoperatively, although AMH recovered to baseline at 3 or 6 months.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similar to RT regarding the effect of uterine surgery on ovarian reserve, Aharon et al reported on AMH before and after myomectomy 14 . Their study found a significant decrease in AMH at 2 weeks postoperatively, although AMH recovered to baseline at 3 or 6 months.…”
Section: Discussionmentioning
confidence: 89%
“…Similar to RT regarding the effect of uterine surgery on ovarian reserve, Aharon et al reported on AMH before and after myomectomy. 14 Their study found a significant decrease in AMH at 2 weeks postoperatively, although AMH recovered to baseline at 3 or 6 months. This finding indicates that uterine surgical stress from RT and myomectomy may cause a temporary decrease in AMH levels in the early postoperative period.…”
Section: Discussionmentioning
confidence: 92%
“…Fan for their interest in our article in the December 2022 issue. 1 The authors suggest that patients with polycystic ovarian syndrome (PCOS) should be excluded from the study due to the association between PCOS and elevated anti-müllerian hormone (AMH) levels. Our study performed a paired analysis in which postoperative AMH levels were compared with the patient's baseline AMH level.…”
Section: In Replymentioning
confidence: 99%
“…In the December 2022 issue, Aharon et al 1 Patients with polycystic ovarian syndrome (PCOS), especially those with hyperandrogenism, obesity, or both, are more likely to have metabolic disorders 2 and to develop type 2 diabetes. 3 In these patients, AMH has been described as elevated.…”
Section: Association Of Myomectomy With Anti-mu ¨Llerian Hormone Leve...mentioning
confidence: 99%
See 1 more Smart Citation